2013
DOI: 10.3892/br.2013.157
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of microRNAs, genes and their regulation in human bladder cancer

Abstract: Abstract. Bladder cancer (BC) is the fifth most common malignancy occurring worldwide and a significant cause of cancer-related morbidity and mortality. Although BC is a serious health issue, studies available concerning the relationship of genes, microRNAs (miRNAs) and their host genes has been lacking. In the present study, we assessed experimentally validated data from various sources that reported the effect of miRNA on various diseases, miRNA targeting of mRNAs, and combined these data with initial transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…MicroRNAs (miRNAs) are generally non‐protein‐coding RNAs of 20–22 nucleotides . They can bind and regulate the transcription or translation of mRNA and play biological roles in different diseases . Previous studies have shown that miR‐324‐5p can bind and inhibit Mtfr1 to alleviate I/R injury after MI .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are generally non‐protein‐coding RNAs of 20–22 nucleotides . They can bind and regulate the transcription or translation of mRNA and play biological roles in different diseases . Previous studies have shown that miR‐324‐5p can bind and inhibit Mtfr1 to alleviate I/R injury after MI .…”
Section: Discussionmentioning
confidence: 99%
“…23 They can bind and regulate the transcription or translation of mRNA and play biological roles in different diseases. 24,25 Previous studies have shown that miR-324-5p can bind and inhibit Mtfr1 to alleviate I/R injury after MI. 22 Through bioinformatics analysis, we confirmed that miR-324-5p could bind Mtfr1 in the 3 0 UTR.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of coexpression-type networks has been used previously to identify genes and proteins of increased importance to controlling system-wide host responses [10,[12][13][14][15]. The topological locations of genes in these networks can be used to identify hubs, genes that are connected to many other genes and therefore may be exerting a regulatory influence, and topological bottlenecks, genes that bridge disparate sub-networks and may serve as mediators of transitions between system states [16][17][18]. Recently, a node's participation in network motifs in directional networks was shown to be an effective predictor of importance [19].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences show that aberrant expression of miRNAs plays significant roles in diverse biological processes such as development, differentiation, growth, and metabolism [13][14][15][16]. Meanwhile, deregulations of miRNAs are observed in a wide range of cancers, including breast cancer, gastric cancer, hepatocellular carcinoma, bladder cancer, osteosarcoma and glioblastoma [17][18][19][20][21][22][23]. MiRNAs can function either as tumor suppressor genes or oncogenes during tumor development and progression [23][24][25].…”
Section: Introductionmentioning
confidence: 99%